Case finding and therapy for chronic viral hepatitis in primary care (HepFREE): a cluster-randomised controlled trial. (January 2019) - Flanagan, Stuart; Kunkel, Jan; Appleby, Victoria; Eldridge, Sandra E; Ismail, Sharif; Moreea, Sulleman; Griffiths, Christopher; Walton, Robert; Pitt, Martin; Salmon, Andrew; Madurasinghe, Vicithranie; Barnes, Eleanor; et al.
Summary: Background: The prevalence of viral hepatitis (hepatitis B virus and hepatitis C virus) in migrants is higher than among the general population in many high-income countries. We aimed to determine whether incentivising and supporting primary-care physicians in areas with a high density of migrants increases the numbers of adult migrants screened for viral hepatitis. Methods: HepFREE was a multicentre, open, cluster-randomised controlled trial in general practices in areas of the UK with a high density of migrants (Bradford, Yorkshire, and northeast and southeast London). Participants were adult patients (aged 18 years or older) in primary care, who had been identified as a first or second generation migrant from a high-risk country. General practices were randomly assigned (1:2:2:2:2) to an opportunistic screening (control) group or to one of four targeted screening (interventional) groups: standard (ie, hospital-based) care and a standard invitation letter; standard care and an enhanced invitation letter; community care and a standard invitation letter; or community care and an enhanced invitation letter. In control screening, general practitioners (GPs) were given a teaching session on viral hepatitis and were asked to test all registered migrants. In the intervention, GPs were paid a nominal sum for setting up searches of records, reimbursed for signed consent forms, and supported by a dedicated clinician. Patients who were eligible for testing and tested positive for viral hepatitis in the intervention groups were eligible to enrol in a second embedded trial of community versus hospital based care. The primary outcomes were the proportion of patients eligible for screening, the proportion of those eligible who were sent an invitation letter in the intervention groups, the uptake of viral hepatitis screening (in the intention-to-treat population), the proportion of patients who tested positive for viral hepatitis, the proportion who complied with treatment, and the cost-effectiveness of the intervention. This trial is registered with ISRCTN, number ISRCTN54828633. Findings: Recruitment and testing ran from Oct 31, 2013, to Feb 4, 2017, and each practice recruited for 18 consecutive calendar months. We approached 70 general practices in three areas with a high density of migrants, of which 63 general practices agreed to participate. Five practices withdrew and 58 practices were randomly assigned: eight to control and 50 to an intervention. In control practices, 26 046 (38·4%) of 67 820 patients who were initially registered were eligible for testing, as were 152 321 (43·3%) of 351 710 patients in the interventional groups in London and Bradford. Of 51 773 randomly selected eligible patients in the intervention groups in London and Bradford, letters were sent to 43 585 (84·2%) patients. In the eight control general practices, screening was taken up by 543 (1·7%) of 31 738 eligible participants, which included 5692 newly registered patients. However, in the 50 general practices that used the intervention, screening was taken up by 11 386 (19·5%) of 58 512 eligible participants (including 6739 newly registered patients; incidence rate ratio 3·70, 95% CI 1·30–10·51; p=0·014) and this intervention was cost-effective. 720 (4·5%) of 15 844 patients who received a standard letter versus 1032 (3·7%) of 28 095 patients who received the enhanced letter were tested (0·70, 0·38–1·31; p=0·26). In the control group, 17 patients tested positive for viral hepatitis, as did 220 patients (one with a co-infection) in the intervention groups. In the embedded study, 220 patients were randomly assigned to either hospital-based care or community care; 80 (87·9%) of 91 patients in the hospital setting complied with treatment versus 105 (81·4%) of 129 patients in the community setting. The intervention was cost-effective at willingness to pay thresholds in excess of £8540. One serious adverse event (thyroiditis) was noted. Interpretation: Screening migrants for viral hepatitis in primary care is effective if doctors are incentivised and supported. Community care is expensive and there is no evidence that this offers benefits in this setting or that bespoke invitation letters add value. We suggest that bespoke invitation letters should not be used, and we suggest that outreach, community-based services for migrants should not be developed. Funding: National Institute for Health Research.